2012
DOI: 10.1017/s1751731111001819
|View full text |Cite
|
Sign up to set email alerts
|

Use of different areas of pen by growing rabbits depending on the elevated platforms’ floor-type

Abstract: The addition of platforms to rabbit cages increases their accessible area and provides rabbits greater freedom and mobility. Different types of platforms enable rabbits to situate themselves where they are most comfortable. The objective of this experiment was to analyse preference of growing rabbits between different areas of the pen depending on the elevated platforms' floor-type. Pens with a basic area of 0.84 m 2 were equipped with platforms of 0.42 m 2 . Three types of flooring of the elevated platforms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The platform design can also affect rabbit preference and use of the different pen areas. Growing rabbits kept in groups (14 animals/pen) preferred to stay under the platforms when these had a solid floor or deep-litter floor, rather than a wire-net floor [27]. Nevertheless, in the case of pens with the wire-net platforms, more rabbits stayed under platforms equipped with a fixed manure tray compared to those without.…”
Section: Discussionmentioning
confidence: 99%
“…The platform design can also affect rabbit preference and use of the different pen areas. Growing rabbits kept in groups (14 animals/pen) preferred to stay under the platforms when these had a solid floor or deep-litter floor, rather than a wire-net floor [27]. Nevertheless, in the case of pens with the wire-net platforms, more rabbits stayed under platforms equipped with a fixed manure tray compared to those without.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the present experiment the rabbits less frequently stayed under the platforms than in front of the platform, because the rabbits on the platforms may urinate on the pen-mates underneath them. This statement was proven, when rabbits were observed in pens with wire-mesh platforms, more rabbits stayed under it when a manure tray was inserted under the platform than in pens without manure tray (Szendr} o et al 2012). Growing rabbits most often stayed under the platform during the resting period (11:00-17:00) when fewer rabbits were on the platforms so there was less chance of being urinated upon.…”
Section: Preference Among Different Platformsmentioning
confidence: 95%
“…At the same time, rabbits stayed more frequently on the plastic-mesh platforms than on the wire-mesh ones any time of the day, which was in accordance with Mik o et al (2014), who found that rabbit does and their kits spent more time on plastic-mesh platforms then on wire-mesh ones. The plastic-mesh floor was more comfortable for the growing rabbits than the wire-mesh one (Princz et al 2009;Szendr} o et al 2012;Gerencs er et al 2014);…”
Section: Preference Among Different Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recumbent doe (4.5 kg) covered 58.3% of the minimum area, and therefore can easily rest outstretched on the platform. An elevated platform is also recommended for fattening rabbits by the German Animal Welfare Regulations in Farm Animals (2014), even though it is a matter of controversy whether it is beneficial for them (Postollec et al, 2008;Szendrő et al, 2011). This raised area must have a minimum size of 1500 cm 2 , providing each rabbit with at least 300 cm 2 additional space.…”
Section: Discussionmentioning
confidence: 99%